The Service-Learning Educator A Guide to Program Management. - ACTION, Washington, DC. National Center for Service - Learning; ACTION, Washington, DC. National Center for Service - Learning ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1979)
A guide for college and university educators who manage service-learning programs, or programs that support student involvement in the community, is presented. A systematic approach to planning and managing service-learning programs is presented, management functions for supporting a service-learning system are identified, and ideas on implementing these support functions are presented. The following functions that are normally the responsibility of service-learning educators are covered: management functions (e.g., planning, organizing, coordinating); functions related to developing strong service projects in the community (e.g., assessing community needs, developing projects and placements, monitoring results); functions related to facilitating student learning (e.g., helping students identify learning objectives, prepare service-learning agreements, and assess learning); support functions (e.g., recruiting, orienting, and transporting students); and office-related functions (e.g., budgeting, recordkeeping, and personnel management). Information is general enough to apply to programs of different size, complexity, and persuasion. Kinds of service-learning programs, characteristics of programs associated with academic affairs versus student affairs, and program management activities are briefly considered. A large selection of sample forms to aid in needs assessment, management, and evaluation of service-learning programs is included. A list of organizations supporting service-learning and references are also included. (SW)
Availability: National Center for Service-Learning/ACTION, Room 1106, 806 Connecticut Ave., N.W., Washington, DC 20525 (free).
Educational level discussed: Higher Education.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Activism; Administrator Responsibility; College Students; Community Development; Community Programs; Educational Objectives; Higher Education; Needs Assessment; Program Administration; Program Descriptions; Program Development; Program Evaluation; Program Guides; Program Implementation; Public Service; Questionnaires; Records (Forms); School Community Programs; Service Learning; Social Action; Student Evaluation; Student Participation; Student Placement; Student Projects; Guides, Non-Classroom.; Tests/Questionnaires.